PENGARUH JUMLAH PENUMPANG DAN JUMLAH KENDARAAN TERHADAP PENDAPATAN JASA PARKIR DI BANDAR UDARA MUTIARA SIS AL-JUFRI PALU - Syukriawati, Rani (Katalogis, 2016)
This study aims: (1) to describe and analyze the development of the number of passengers, the number of vehicles and parking services revenue at Mutiara Sis Al-Jufri Airport in Palu; and (2) to acknowledge and analyze the impact of the number of passengers and Â vehicles on the parking fee income at the airport of Mutiara Sis Al-Jufri in Palu with partially or simultaneously. Data were analyzed by analysis of growth (trend) and multiple linear regression analysis, the results show that there are an increase of the growth of parking services revenue at the airport of Mutiara Sis Al-Jufri Palu, and the number of passengers and vehicles with partial and simultaneous have significant impact on the airport parking services revenue at Mutiara Sis Al-Jufri Palu Airport